DEVELOPMENT OF NATIONAL LAW IN PERSPECTIVE TRANSCENDENTAL PARADIGM - Taryono Taryono; Arie Purnomosidi (Surakarta Law and Society Journal, 2019)
This study aims to analyze and explain development of national law in perspective transcendental paradigm. The results of the study that the fundamental values of national legal order Indonesia which is based on the paradigm of transcendental include: (1) the value of the first foundation: the legal character to protect (protect) and not just govern granted, (2) the value of the second base: laws that embody social justice for all people Indonesia. Social justice and not solely as a destination. However, in the grip of concrete in making laws, (3) The value of the third basic: the law is of the people and contain properties populist, and (4) The value of the basic four: the law is a statement of decency and morality, both in legislation and in implementation as taught in religious teachings (transcendent) and customs of our people.